2021
DOI: 10.1002/cam4.4020
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion for treating cancer‐related fatigue: A multicenter, assessor‐blinded, randomized controlled clinical trial

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
3
17
0
2
Order By: Relevance
“…These results align well with a growing body of literature demonstrating the ability of acupuncture and moxibustion to help alleviate the fatigue [ 26 , 27 ] and insomnia [ 28 , 29 ] experienced by patients diagnosed with or recovering from cancer. Strikingly, ILM failed to significantly improve fatigue as compared to sham treatment at the end of the treatment interval despite exhibiting significant benefits at later follow-up time points, consistent with the results of another recent moxibustion trial [ 27 ]. This suggests that ILM can exhibit prolonged benefits as a treatment for CRF, although the underlying mechanisms remain to be fully clarified.…”
Section: Discussionsupporting
confidence: 86%
“…These results align well with a growing body of literature demonstrating the ability of acupuncture and moxibustion to help alleviate the fatigue [ 26 , 27 ] and insomnia [ 28 , 29 ] experienced by patients diagnosed with or recovering from cancer. Strikingly, ILM failed to significantly improve fatigue as compared to sham treatment at the end of the treatment interval despite exhibiting significant benefits at later follow-up time points, consistent with the results of another recent moxibustion trial [ 27 ]. This suggests that ILM can exhibit prolonged benefits as a treatment for CRF, although the underlying mechanisms remain to be fully clarified.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies point out that phlegm and turbidity are mainly formed due to the deficiency of yang in the spleen and stomach and the malfunction of healthy transportation, and the pathogenesis of this type of vertigo is the deficiency of yang and yin, and the original deficiency and the symptoms are real, while phlegm and beverages are yin evils, which condense when they get cold and dissolve when they get warm. Moxibustion [ 9 ] and ear acupressing bean therapy [ 10 ] are the treasures of Chinese medicine, and research on moxibustion and ear acupressing bean therapy for vertigo has been in constant development in recent years. Studies [ 11 , 12 ] have shown that stimulating the corresponding response points and acupuncture points in the auricle can help regulate the qi and blood of the internal organs, balance yin and yang, unblock the meridians, and tonify the kidneys and strengthen the spleen, thus achieving a calming and tranquilizing effect and stopping dizziness.…”
Section: Introductionmentioning
confidence: 99%
“…Such as, moxibustion can inhibit nausea and vomiting after chemotherapy [ 28 , 29 ]. In addition, moxibustion can also be used to treat cancer-related fatigue [ 30 ]. The mechanism of moxibustion therapy for cancer is still unclear.…”
Section: Discussionmentioning
confidence: 99%